Parental Involvement in Supporting Children's Independence and Providing a Balanced Understanding of Gender - Erwin Bunga Sapan; Isobeliana Musrini (Atfaluna: Journal of Islamic Early Childhood Education, 2024)
This study examines parental involvement in fostering children's independence and promoting an early understanding of gender equality. Using a qualitative case study approach at SILO Makale Kindergarten, South Sulawesi, data were collected through interviews, observations, and documentation. The findings indicate that active parental involvement, particularly when grounded in gender-responsive practices, positively influences children's independence and their comprehension of gender equality. Children raised in such environments tend to demonstrate greater autonomy and a more equitable perspective on gender roles. Conversely, limited parental attention and engagement were associated with higher dependency in daily activities. The study also reveals that gender education at the preschool level remains underdeveloped, which may hinder children's understanding of gender roles. Based on these results, the study recommends that parents actively engage in practices that support both independence and gender equality, while preschool institutions should begin systematically integrating gender equality concepts into early childhood education.